2021
DOI: 10.3389/fcell.2021.722224
|View full text |Cite
|
Sign up to set email alerts
|

Immune Microenvironment Change and Involvement of Circular RNAs in TIL Cells of Recurrent Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma is a malignant tumor that is highly prevalent in southern China and the Southeast Asian belt. Recent studies have shown that the T cells play important regulatory roles in tumorigenesis and progression. We test TIL cell of recurrent nasopharyngeal carcinoma and primary nasopharyngeal carcinoma cell. We found that T cell change in recurrent nasopharyngeal carcinoma and primary nasopharyngeal carcinoma cell. Based on GEO database, we selected differently expressed circRNAs in nasopharyng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Predina et al [33] demonstrated that recurrent tumours and draining lymph nodes are infiltrated with M2 macrophages and CD4 + Foxp3 + regulatory T cells. Furthermore, the composition of tumour-infiltrating T cells significantly changes during the recurrence of cancer, especially the increase of Treg and the CD4 + /CD8 + ratio [34]. In the CD4 + T cells fractions, T helper 1/T helper 2 (Th1/Th2) cells are considered to differentially up-regulate PD-L1 and PD-L2 expression on inflammatory macrophages [35].…”
Section: Discussionmentioning
confidence: 99%
“…Predina et al [33] demonstrated that recurrent tumours and draining lymph nodes are infiltrated with M2 macrophages and CD4 + Foxp3 + regulatory T cells. Furthermore, the composition of tumour-infiltrating T cells significantly changes during the recurrence of cancer, especially the increase of Treg and the CD4 + /CD8 + ratio [34]. In the CD4 + T cells fractions, T helper 1/T helper 2 (Th1/Th2) cells are considered to differentially up-regulate PD-L1 and PD-L2 expression on inflammatory macrophages [35].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs (circ0000831, circ005019, circ0031584 circ0006935 and circ0001730) have been revealed to induce changes in the TME of recurrent nasopharyngeal carcinoma. Altered distribution of immune cells and a decline in the ratio of CD4 + /CD8 + T cells were observed in the presence of these circRNAs (225). Targeting T cell activation by inhibiting the checkpoints such as the PD-1/PD-L1 pathway is termed checkpoint immunotherapy (226).…”
Section: Role Of Circrnas In Immunotherapy and Tumor Immunologymentioning
confidence: 99%
“…With the development of treatment techniques, the 5-year overall survival rate of NPC has reached 50-64%. However, 10-20% of patients with NPC still experience locoregional recurrence, metastasis, invasion, and radio resistance [4][5][6]. Therefore, determining biomarkers and potential mechanisms affecting carcinogenesis and recurrence is essential for developing a more personalized treatment for patients with NPC.…”
Section: Introductionmentioning
confidence: 99%